Persistence Development across the Transition to School: A Latent Profile Transition Analysis. Issue 1 (2nd January 2023) - Kälin, Sonja; Roebers, Claudia M.; Oeri, Niamh
ABSTRACT: Research Findings : The goal of this longitudinal study was to examine persistence development during the transition to school. The sample consisted of N = 88 children from Caucasian, middle-class families (51% female). Participants were recruited through advertisement in public kindergartens and were tested twice, in kindergarten (mean age = 73.4 months) and second grade (mean age = 94.6 months). We computed latent profile analyses to examine different behavioral approaches during a persistence task. Furthermore, we analyzed change and stability in these task approaches during the transition from kindergarten to elementary school. Analyses revealed three different latent profiles for both measurement points: a persistent profile, a mixed profile, and an engaged-disengaged profile. Most children were best described by the persistent profile, which was also the most stable profile over time (stability rate: .74). A less persistent task approach characterized children in the mixed profile and engaged-disengaged profile. Covariate analyses revealed differences between the latent profiles in terms of cognitive flexibility (η 2 = .102) and in terms of learning-related behavior (η 2 = .085). Practice or Policy : The results indicate that persistence difficulties can be found in two different task approaches. Consequently, we argue that these children need different types of assistance to address their persistence difficulties. Overall, the findings offer new possibilities to develop suitable intervention programs to support the ability to persist in the face of a challenge.